The impact of seasonal sulfate-methane transition zones on methane cycling in a sulfate-enriched freshwater environment - Kleint, Jan F.; Wellach, Yannic; Schroll, Moritz; Keppler, Frank; Isenbeck-Schröter, Margot (Limnology and oceanography, 2021)
Lake Willersinnweiher located in south-western Germany is a small eutrophic gravel pit lake fed by sulfate-enriched groundwater. The aim of this study was to investigate the total methane (CH4) mass balance of Lake Willersinnweiher with a particular focus on the interaction of carbon and sulfur cycling within the lake sediments and the redoxcline of the water column. Our results show that Lake Willersinnweiher permanently releases CH4 to the atmosphere throughout the whole year 2018 at rates ranging from 5 to 120 mol d−1. Sediment data show the presence of intense anaerobic oxidation of CH4 in the upper sediment layers during early summer. Here, CH4 is most likely consumed via sulfate in sulfate-methane transition zones (SMTZs) that have been observed for a few specific freshwater environments only. Seasonal dynamics in biogeochemical processes trigger the non-steady state conditions within the sediments and the CH4 consumption in the SMTZs. In parallel, CH4 released from the sediments is completely consumed by aerobic oxidation processes in the redoxcline indicated by minimum CH4 concentrations with high δ13C-CH4 values. This zone acts as an effective barrier, minimizing CH4 release into the surface water and the atmosphere and thus CH4 oversaturation along with near-atmospheric isotopic composition indicate the presence of an additional CH4 source in the epilimnion of Lake Willersinnweiher.